The initial clinical application of standard PCNL combined with visual needle nephroscope in the treatment of complex renal calculi by holmium YAG laser: a retrospective case series study - Engo Ovone Yanne; Bai Lin Wu; Cong Li; Jiaqiao Zhang; Xiao Yu; Xiaolin Guo; Lei Cui; Huan Yang (BMC Urology)
Abstract This study aims to evaluate the feasibility, safety, and effectiveness of an optimized treatment approach for complex renal calculi, utilizing visual needle nephroscopy in conjunction with standard PCNL and holmium YAG laser. We collected data from 62 patients diagnosed with complex kidney stones who underwent this combined procedure using the visual needle nephroscope (Needle-perc®, Youcare Tech, Wuhan, China). The percutaneous nephroscopic working channel was established by visual needle nephroscope, and the primary channel was expanded to 20 F to treat most of the main body of the calculi with a 550 μm holmium laser fiber. Visual needle nephroscope was used to locate the renal calyx where the residual calculi were located for precise puncture as a secondary channel, and the residual stones were treated by a 200 μm holmium laser fiber. Clinical data were collected, and intraoperative variables, postoperative complications and outcomes were assessed. All 62 patients successfully completed the operation without severe complications. The S.T.O.N.E. score of 62 patients before operation was 10.5 ± 0.9 points and above, of which the N score was more than 2 points. The average operation time was (65.5 ± 12.7) minutes, and the average hospital stay was (7.3 ± 2.1) days. After operation, 2 patients developed a fever, which improved after symptomatic treatment by intravenous antibiotics. 4 patients had clinically significant residual fragments, and the stone-free rate of primary operation was 93.5% (58/62). The optimized operation for the treatment of complex renal calculi based on standard PCNL combined with visual needle nephroscope by holmium YAG laser has good feasibility, safety and effectiveness.